PEMIKIRAN AL-GHAZALI TENTANG PENDIDIKAN AKHLAK - Enok Rohayati (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
Several years ago, exactly on March, 12-15, 1997, we experienced a terrible incident during the New Order government, the fall of the New Order regime has resulted many victims in this country. It is very naive to discuss from the education point of view. Based on the background of the above problems, the problems can be formulated as follows: How are al-Ghazali's ideas about moral education? The objective of this research is to find out how the concept of Moral Education According to Imam al-Ghazali. Data collected in this study were analyzed with descriptive analytic method. Based on the analysis, it can be concluded that the Morals according to Al-Ghazali is something settles in life and appears in the action easily without the need of thinking first. Morals are not deeds, strengths, and knowledge. Morals are